Spinal Calcrl+ neurons amplify mechanical itch signaling via synaptic plasticity in chronic itch model - Huifeng Jiao; Qi Dai; Zhaoting Li; Min Yuan; Guoqun Xu; Yingxin Tian; Guangyuan Su; Yu Zhang; Chong Sun; Shunqi Wang; Chaolin Ma; Haili Pan (PLoS ONE, 2025)
Chronic itch, a devastating dermatological disorder, lacks targeted therapies due to incomplete understanding of its neural circuitry. Building on seminal studies that identified neuropeptide Y (NPY) inhibitory interneurons and their downstream urocortin 3-positive (Ucn3 + )/Y1R-expressing neurons, calcitonin receptor-like receptor-positive (Calcrl + ) neurons, identified as spinal projection neurons, have been proposed to contribute to mechanical itch signaling, though their underlying mechanistic role remains undefined. In the present study, using chemogenetic manipulation, behavioral tests, morphological assays and electrophysiological approaches in allergic contact dermatitis, atopic dermatitis and Psoriasis chronic itch models, we elucidates the role of spinal Calcrl + neurons in mechanical itch pathophysiology. We report that: (1) Chemogenetic activation of spinal Calcrl + neurons induces enhanced mechanical itch sensitization and increased spontaneous scratching behaviors in naïve mice; (2) Chemogenetic inhibition of spinal Calcrl + neurons alleviates mechanical itch sensitization and spontaneous scratching behaviors in chronic itch models; (3) Chronic itch enhances intrinsic excitability of Calcrl+ neurons in chronic itch model; (4) Aβ-fiber-evoked synaptic excitation of Calcrl+ neurons is significantly amplified in chronic itch, accompanied by reduced inhibitory input. Our study elucidates a pathological synaptic plasticity mechanism in chronic itch, wherein spinal Calcrl+ neurons undergo hyperexcitability, enhanced Aβ-fiber-evoked excitatory transmission and reduced inhibitory input. These findings establish a spinal Calcrl-dependent circuit as a critical driver of mechanical itch sensitization, providing actionable targets for disrupting maladaptive itch circuits in dermatological disorders.